Clinicopathological risk factors for gastric cancer: a retrospective cohort study in China. Issue 9 (20th September 2019) - Hu, Kongwang; Wang, Shuaili; Wang, Zikun; Li, Longlong; Huang, Zhiguo; Yu, Weiqiang; Chen, Zhongxue; Wu, Qing-Fa
Abstract : Objective: To examine the potential clinicopathological factors affecting the prognosis of patients with gastric cancer after surgical treatment in China. Methods: Between 1 January 2001 and 31 December 2012, a total of 716 patients aged 22–84 years with gastric cancer were enrolled in the study. Survival analysis techniques including log rank test and Cox proportional hazard regression model were applied to evaluate the prognostic significance of clinicopathological characteristics in terms of survival time. Results: Of the 24 demographic and pathological variables collected in the data, 16 prognostic factors of gastric cancer were found to have statistically significant influences on survival time from the unadjusted analyses. The adjusted analysis furtherly revealed that age, age square, lymph node metastasis rate group, tumour size group, surgical type II, number of cancer nodules, invasion depth group and the interaction between surgical type II and tumour size group were important prognosis and clinicopathological factors for gastric cancer in Chinese. Conclusion: Our study with relatively large sample size and many potential risk factors enable us to identify independent risk factors associated with the prognosis of gastric cancer. Findings from the current study can be used to assist clinical decision-making, and serve as a benchmark for the planning of future prognosis and therapy for patients with gastric carcinoma.